My 4 in 1 Math Plate - Che Hashim, Iznida Hayu; Che Hashim, Izrahayu (Multidisciplinary Applied Research and Innovation, 2021)
Counting is a critical skill in human life. Even if they already recognize numbers, Special Education students with learning disabilities typically struggle with mastering addition, subtraction, multiplication, and division skills. The primary reason for this is that they recognize numbers solely on the basis of their appearance, and some of these students simply memorize. Thus, we developed an innovation using the ’My 4 in 1 Math Plate’ tool to assist Special Education students in developing their ability to perform addition, subtraction, multiplication, and division operations. Initially, this study enrolled five (5) Special Education students from PPKI Bestari and two (2) Special Education students from PPKI Perkasa in SJKC Sin Min’s Special Education Integration Program. This study was conducted using an action research design. The data were analyzed descriptively using observations, video recordings, interviews, photographs, and checklists. The study’s findings indicate this tool can assist Special Education students in developing their ability to perform addition, subtraction, and division operations. Using this tool also helps teachers in planning and implementing student-centered (PdPc) activities. Additionally, this study can serve as a substitute for the counting method, with a 100% accuracy rate compared to the conventional counting method.